LONELINESS AND MOBILE PHONE - Tan, Cetin; Pamuk, Mustafa; Donder, Aysenur (Elsevier Science Bv, 2013)
The aim of this study is to analyse loneliness of university students according to mobile phone addiction, daily phone use time and gender. Survey model is used for this research. To collect data; personel information form, problematic mobile phone use scale, and UCLA-loneliness scale were applied for 527 students who are from different Departments of Faculty of Education at Firat University. To analyse these data; correlation, t test, one way variance (ANOVA) analysis and Scheffe test were used. Results revealed that loneliness was significantly associated with problematic mobile phone use (r=.35) Furthermore, there were significant differences between loneliness and independent variables (gender, mobile phone addiction and daily phone use time). The results of the study were discussed together with the results of different studies and suggestions were made. (C) 2013 The Authors. Published by Elsevier Ltd.
13th International Educational Technology Conference -- OCT 30-NOV 01, 2014 -- Lisbon, PORTUGAL
Keywords: loneliness; mobile phone; mobile phone addiction